African wax print textiles - Grosfilley, Anne; French, Rachel (Munich : Prestel, 2018)
This groundbreaking book reveals the complex origins of African wax print textiles. In beautifully illustrated chapters, Anne Grosfilley traces the process of printing and dying the fabric, involving wax or indigo, to its West Indian roots. She also explores the differences of mass-produced and artisanally sourced fabrics, tracking where textiles go from the manufacturing centers to markets and cities throughout Africa and the world. Grosfilley offers the fruits of her own passionate research as she profiles a variety of individuals from rural vendors to trendsetting fashionistas. This eye-opening study celebrates the enormous variety of African fabric styles and uses, and explores the complex interconnections between the continent and colonialism and between modern technology and Old World practices.
Includes bibliographical references.
Keywords: Batik -- Africa, West; Clothing and dress -- Africa, West; Textile design -- Africa, West; Textile fabrics -- Africa, West; Textile fabrics; Textilier; Västafrika